Plasticity of GABAA receptor diffusion dynamics at the axon initial segment - Muir, James; Kittler, Josef T. (Frontiers in Cellular Neuroscience, 2014)
The axon initial segment (AIS), a site of action potential initiation, undergoes activity-dependent homeostatic repositioning to fine-tune neuronal activity. However, little is known about the behaviour of GABAA receptors (GABAARs) at synapses made onto the axon and especially the AIS. Here, we study the clustering and lateral diffusion of GABAARs in the AIS under baseline conditions, and find that GABAAR lateral mobility is lower in the AIS than dendrites. We find differences in axonal clustering and lateral mobility between GABAARs containing the α1 or α2 subunits, which are known to localize differentially to the AIS. Interestingly, we find that chronic activity driving AIS repositioning does not alter GABAergic synapse location along the axon, but decreases GABAAR cluster size at the AIS. Moreover, in response to chronic depolarization, GABAAR diffusion is strikingly increased in the AIS, and not in dendrites, and this is coupled with a decrease in synaptic residency time of GABAARs at the AIS. We also demonstrate that activation of L-type voltage-gated calcium channels is important for regulating GABAAR lateral mobility at the AIS during chronic depolarization. Modulation of GABAAR diffusion dynamics at the AIS in response to prolonged activity may be a novel mechanism for regulating GABAergic control of information processing.